SCIENTIFIC AND THEORETICAL FOUNDATIONS OF INNOVATIVE MANAGEMENT OF THE GREEN ECONOMY - Baxtiyorova Dildora, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article explores the scientific and theoretical foundations of innovative management within the green economy framework. As the global community seeks sustainable solutions to environmental degradation and resource depletion, the integration of innovation into economic management becomes vital. The paper discusses the principles of green economy, the role of innovation in sustainable development, and theoretical models that support the transition towards eco-friendly economic systems. It also outlines strategic recommendations for policy-makers and businesses to implement innovative management practices that align with environmental goals.